Alternation, Transition, and Regime Change in Mexico: Is the Glass Half Full or Empty? - Pansters, Wil (European Review of Latin American and Caribbean Studies, 2011)
– Vuelta en U. Guía para entender y reactivar la democracia estancada, by Sergio Aguayo Quezada. México D.F.: Taurus, 2010.– Consolidating Mexico’s Democracy. The 2006 Presidential Campaign in Comparative Perspective, edited by Jorge I. Domínguez, Chappell Lawson and Alejandro Moreno. Baltimore: The Johns Hopkins University Press, 2009.– El centro dividido. La nueva autonomía de los gobernadores, by Rogelio Hernández Rodríguez. Mexico City: El Colegio de México, 2008. – México. ¿Un nuevo regimen politico? edited by Octavio Rodríguez Araujo. México D.F.: Siglo XXI, 2009. – Mexico’s Democratic Challenges. Politics, Government, and Society, edited by Andrew Selee and Jacqueline Peschard. Washington/Stanford: Woodrow Wilson Center Press/Stanford University Press, 2010.– Savage Democracy. Institutional Change and Party Development in Mexico, by Steven T. Wuhs. University Park, Pennsylvania: The Pennsylvania State University Press, 2008.